The Influence of Al-Qira’at Al-Asyr on the Exegesis of Legal Verses in Tafsir Marah Labid by Nawawi Al-Bantani: A Historical and Analytical Study - Abdul Rohman; Barikli Mubaroka; Amin; Irfan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
The interpretation of the Qur’an often involves various tools such as linguistic analysis, historical context, and qiraat (variant readings), which significantly influence interpretative outcomes. This article examines the impact of the ten qiraat on legal verses in Nawawi Al-Bantani’s exegesis, Tafsir Marah Labid. Employing a qualitative content analysis method, the primary source is the Tafsir Marah Labid. Findings show that Nawawi Al-Bantani, a prominent Nusantara scholar adhering to the Shafi’i school of thought, was heavily influenced by the ten qiraat (al-Qiraat al-’Asyr) in his interpretation of legal verses. This influence is evident in legal debates where Nawawi often favored qiraat, which aligned with Shafi’i legal rulings. Nonetheless, his approach is commendable as he consistently selected sahih (authentic) qiraat conforming to the Uthmanic script.